Bioaccumulation of Lead and Cadmium Residues in Fish and Shrimp at Different Stages of Development in the Nokoué-Channel Lagoon Complex in Southern Benin - YOUSSAO ABDOU KARIM, ALASSANE; GBAGUIDI, ACAKPO NONVIGNON MAGLOIRE; Azokpota, Emmanuel; DOVONON, Léonce Comlan Firmin; SAIZONOU, Mickael Kpessou Vitus; MAMA, DAOUDA; SOCLO, HOUÉNOUKPO HENRI (My University, 2018)
At different stages of their development, we studied the bioaccumulation of lead and cadmium residues in fish species Tilapia guineensis, Sarotherodon melanotheron, Hemichromis fasciatus in Nokoué lake and Dicentrarchus labrax, Selene dorsalus and shrimp in Cotonou Channel. The methodology adopted was to identify the species and collect the muscles in these different species of fish and shrimp at different stages of their life's development. Fishery products in situ and water samples taken are sent to the laboratory in coolers maintained at 4 ± 5 °C for the quantitative analysis of lead and cadmium residues by spectrophotometry. The results of the analysis show that lead residues are more accumulated in younger species than in adults in Sarotherodon melanotheron and Hemichromis fasciatus, unlike Tilapia guineensis. On the other hand, cadmium is weakly present in water and in aquatic fauna and some traces of cadmium residues are found in the Cotonou Channel, notably at the height of Dantokpa market. The water-based lead bioconcentration factors are significantly greater than the unit showing the predominance of particulate lead exposures of sedimentary origin. The lifestyle of the fish species would be the main factor explaining these results.
Keywords: Channel-nokoué; Lead; Cadmium; Bioconcentration; Fish; Shrimp.